Mini Review: Analysis of The Influence of Work Environment on SMAW (Shielded Metal Arc Welding) Results - Nursafitri, Gita; Indriawan, Ari Dwi Nur (Sainteknol : Jurnal Sains dan Teknologi, 2025)
This study aimed to systematically investigate the influence of key environmental factors on the quality of Shielded Metal Arc Welding (SMAW) outcomes. The welding process, although widely applied across various industrial sectors, remains highly sensitive to variations in its surrounding environment. Through a systematic review of previous research, academic articles, and industrial reports, this study identified temperature, air pollution, and ventilation as the most critical environmental variables. Temperature fluctuations were found to cause weld defects such as porosity and cracking. Optimal welding performance was observed within an ambient temperature range of 10°C to 30°C, with several studies suggesting narrower optimal ranges of 15°C to 28°C or 16°C to 27°C. Temperatures below 10°C accelerated weld cooling, increasing the risk of cold cracks, while those above 30°C degraded electrode coatings, leading to porosity. Moreover, airborne contaminants—including Fe₂O₃, MnO, and CO concentrations exceeding 5 mg/m³—were shown to reduce tensile strength by 15% to 20%. Adequate ventilation, particularly using mechanical systems like local exhaust ventilation (LEV), was more effective than natural ventilation in enclosed welding environments. Integrating air filtration with precise temperature control could reduce weld defects by up to 50%. The study provides practical recommendations for improving weld quality and promoting industrial safety.